PEMBUATAN PAPAN EDUKASI MASYARAKAT TENTANG PEMILAHAN SAMPAH - Joni Sasmito; Muhammad Fawwaz Zarqy Al Ghifari (Jurnal Pengabdian Kompetitif, 2026)
Waste management remains a persistent environmental challenge in many rural areas of Indonesia, including Saloloang Village, Penajam Paser Utara Regency. Although the community demonstrates strong social cohesion, the absence of structured and accessible educational media on waste segregation has limited the effectiveness of local environmental management efforts. This community service program aimed to enhance public awareness and promote proper waste segregation practices through the design, production, and installation of a bilingual educational board in the coastal area of the village. A descriptive participatory approach was employed, involving site observation, informal consultation with local stakeholders, content development based on visual communication principles, and collaborative implementation. The educational board presents clear information on organic and inorganic waste categories and incorporates an interactive convex mirror element to increase visual engagement and attract visitors’ attention. Observational findings after installation indicated positive responses from both residents and visitors, particularly school-aged children, who showed interest in reading and interacting with the board. The initiative demonstrates that integrating informative content with creative visual elements can strengthen environmental messaging in public spaces. However, the evaluation was limited to descriptive observations without quantitative measurement of behavioral change. Overall, the program contributes to reinforcing community-based waste management efforts by providing a sustainable visual communication medium in a high-traffic coastal area